Do Co-morbid Anxiety Disorders Predict Drinking Outcomes in Women with Alcohol Use Disorders? - Farris, Samantha G. (Oxford University Press, 2012)
Aims: It is unclear whether co-morbid anxiety disorders predict worse drinking outcomes during attempts to change drinking behavior. Studies have yielded mixed results, and have rarely examined drinking outcomes based on a specific type of anxiety disorder. Women with alcohol use disorders (AUDs) are of particular interest as they are at risk for co-morbid anxiety [Kessler et al. (1997) Lifetime co-occurrence of DSM-III-R alcohol abuse and dependence with other psychiatric disorders in the national co-morbidity survey. Arch Gen Psychiat 54:313–21]. Methods: Participants were 260 women with AUDs participating in an alcohol-treatment outcome studies. The Timeline Follow-Back was used to assess drinking frequency (percent days drinking)  prior, within and 6 months post-treatment. The current study tested the hypothesis that having at least one lifetime anxiety disorder diagnosed at baseline using the Structured Clinical Interview for DSM Disorders would be associated with more drinking at all study time points. Exploratory analyses examined patterns of drinking outcomes by specific anxiety diagnoses. Results: Lifetime anxiety diagnosis was linked to poorer drinking outcomes post-treatment (β = 0.15, P = 0.020), despite less frequent drinking prior to treatment. Analyses by specific anxiety diagnosis indicated that generalized anxiety disorder predicted poorer drinking outcomes within treatment (β = 0.14, P = 0.018) and during follow-up (β = 0.16, P = 0.014). Conclusion: Co-morbid anxiety problems complicate treatment for AUDs among women. Further, specific anxiety disorders should be evaluated as distinct constructs as evidenced by the differential outcomes related to generalized anxiety disorder. Implications for treatment development for women with AUDs are discussed.